Cultivating oral proficiency: Harnessing digital technologies to enhance 2nd year students’ speaking skills - Abdulmjeed, Nuha Abdelmjeed Taha; Osman, Eshraga Mohammed Abdalla; Ibrahim, Ezzelden Ibrahim Mohammed (Edelweiss Applied Science and Technology, 2026)
This study aims to investigate the effectiveness of digital technologies on the development of students' speaking skills among the 2nd-year English language learners at the Sudan University of Science and Technology. A descriptive analytical method was applied through the use of a questionnaire, which offers first-hand data that is easily quantifiable. The responses obtained from participants can be simply transformed into a numeric form suitable for quantitative analysis of data. A questionnaire was designed and distributed to 100 male and female participants who were purposefully selected, while 90 questionnaires were collected from 100 participants. The SPSS version 20 program was used to analyze the obtained data. The study findings revealed the following: digital technologies are helpful pedagogical tools that significantly influence students’ speaking skills. Additionally, digital technologies are very effective in helping students increase their speaking skills and reduce students’ anxiety. Furthermore, digital technologies played a vital role in developing students' speaking skills and offer many benefits to students of the University of Science and Technology.